Viewed from above: extracting the built environment from the ancient Purépecha site of Angamuco through development of a new methodology - Harris, Edwin, author; Fisher, Chris, advisor; Leisz, Steve, committee member; Falkowski, Michael, committee member (Colorado State University. Libraries, 2019)
This thesis utilizes commonly used GIS tools to develop a methodology capable of extracting the built environment from the complex topology of the ancient Purépecha site of Angamuco located in Michoacán, Mexico. Unlike lowland areas and coastal regions Angamuco sits upon a volcanic malpaís consisting of rolling hills, small valleys, complex ridgelines, and a multitude of microtopographic features creating a complex physical landscape. This topographically complex landscape creates unique challenges in extracting subtle archaeological features and requires a new methodology to separate the built environment. This new methodology utilizing common GIS tools in a flexible workflow consisting of topographic manipulation, value identification, and analysis preparation. The results of the methodology provides a data set of 87,407 possible archaeological features. These features are all greater than 5m² in area and consist of a wide range of circular to rectilinear, linear, and numerous miscellaneous shaped features throughout the site. The capability of this dataset in further analysis is shown through the application of a density analysis and classification based on the Thinness Ratio to conduct OBIA at the individual feature level. Although, the dataset does require manual clean-up the application of the data to answer certain questions about the urban attributes of the site of Angamuco is valid. Further analysis of this output dataset through GIS can provide detailed answers to questions about urban design for the Purépecha prior to and during the early Empire phase.